Use of Systemic Therapies for Treatment of Psoriasis in People Living with Controlled HIV: Inference-Based Guidance from a Multidisciplinary Expert Panel - Kim A. Papp; Jennifer Beecker; Curtis Cooper; Mark G. Kirchhof; Anton L. Pozniak; Juergen K. Rockstroh; Jan P. Dutz; Melinda J. Gooderham; Robert Gniadecki; Chih-ho Hong; Charles W. Lynde; Catherine Maari; et al. (Adis, Springer Healthcare, 2022)
Abstract Background People living with human immunodeficiency virus (PLHIV) have a similar prevalence of psoriasis as the general population, though incidence and severity correlate with HIV viral load. Adequately treating HIV early renders the infection a chronic medical condition and allows PLHIV with a suppressed viral load (PLHIV-s) to live normal lives. Despite this, safety concerns and a lack of high-level data have hindered the use of systemic psoriasis therapies in PLHIV-s. Objectives We aim to provide a structured framework that supports healthcare professionals and patients discussing the risks and benefits of systemic psoriasis therapy in PLHIV-s. Our goal was to address the primary question, are responses to systemic therapies for the treatment of psoriasis in PLHIV-s similar to those in the non-HIV population? Methods We implemented an inference-based approach relying on indirect evidence when direct clinical trial data were absent. In this instance, we reviewed indirect evidence supporting inferences on the status of immune function in PLHIV. Recommendations on systemic treatment for psoriasis in PLHIV were derived using an inferential heuristic. Results We identified seven indirect indicators of immune function informed by largely independent bodies of evidence: (1) functional assays, (2) vaccine response, (3) life expectancy, (4) psoriasis manifestations, (5) rate of infections, (6) rate of malignancies, and (7) organ transplant outcomes. Conclusions Drug-related benefits and risks when treating a patient with systemic psoriasis therapies are similar for non-HIV patients and PLHIV with a suppressed viral load and normalized CD4 counts. Prior to initiating psoriasis treatment in PLHIV, HIV replication should be addressed by an HIV specialist. Exercise additional caution for patients with a suppressed viral load and discordant CD4 responses on antiretroviral therapy.